Deck the Halls With Boughs of Holly to Soften Evaluations of Service Failure. (November 2018) - Newton, Joshua D.; Wong, Jimmy; Casidy, Riza
Symbols associated with seasonal religious festivals are periodically displayed by service providers, but do these symbols serve more than just a decorative function? Findings from seven experiments suggest they do. In the presence of such symbols, individuals soften their evaluations of a personally experienced service failure encounter. This effect emerges through the activation of forgiveness but only among those with a religious upbringing and only when the encounter involves service failure (rather than neutral service). The softening of service evaluations in the presence of such symbols is reversed, however, when service failure is observed (rather than directed at the self) and when the recipient of that failure is perceived to be vulnerable. Contextual exposure to symbols associated with seasonal religious festivals therefore presents a double-edged sword for managers; depending upon the service failure recipient, these symbols can harden or soften evaluations of the service failure encounter.